Negative impact of litigation procedures on patient outcomes four years after severe traumatic brain injury: results from the PariS-traumatic brain injury study. Issue 17 (14th August 2018) - Bayen, Eléonore; Jourdan, Claire; Ghout, Idir; Pradat-Diehl, Pascale; Darnoux, Emmanuelle; Nelson, Gaëlle; Vallat-Azouvi, Claire; Charenton, James; Aegerter, Philippe; Ruet, Alexis; Azouvi, Philippe
Abstract: Purpose: To analyze the effect of litigation procedures on long-term outcomes in severe traumatic brain injury. Materials and methods: Prospective observational follow-up of an inception cohort including 504 adults with severe traumatic brain injury recruited in 2005–2007 in the Parisian area, France, with initial, one- and four-year outcomes measures. Results: Four years after the traumatic brain injury, 147 patients, out of 257 who survived the acute phase, were assessed. Among these patients, 53 patients declared being litigants and 78 nonlitigants (litigation status was unknown in 16 cases). Sociodemographic characteristics, type of injury and initial severity did not differ significantly between litigants and nonlitigants, except for Injury Severity Score (worse in litigants) and the proportion of road traffic accidents (higher in litigants). One- and four-year outcomes were significantly worse in litigants for autonomy, participation, psychiatric and cognitive function but not quality of life (measured with the Glasgow Outcome Scale-Extended, the working activity status, the Brain Injury Community Rehabilitation Outcome, the Hospital Anxiety and Depression scale, the Neurobehavioral Rating Scale-revised and the Quality of Life after Brain Injury, respectively). Multivariate analyses highlighted litigation procedure as an independent significant predictor of lower autonomy, participation and psychiatric function and tended to predict lower cognitive function, but not lower quality of life, after adjustment for pretrauma characteristics, Injury Severity Score, road traffic accidents and work-related accident status. Conclusions: Patients with severe traumatic brain injury have a worse prognosis when involved in a litigation procedure and require special attention in clinical practice. Implications for rehabilitation: The influence of litigation procedure on health and social outcomes in severe traumatic brain injury is a major issue that entail numerous levels of complexities. A wide range of interactions and factors related to the prolonged process of litigation against a third party may influence recovery. Results from the PariS-Traumatic Brain Injury study suggest that patients with a severe Traumatic Brain Injury who are involved in a litigation procedure within French jurisdiction compensation scheme have a worse prognosis than patients who do not. Health professionals should be aware of the potential adverse effects of litigation procedures on recovery, and provide appropriate interventions and information to patients and families in such cases.